Epidemiology of smoking among Malaysian adult males: prevalence and associated factors - Lim, Kuang Hock; Mohd Ghazali, Sumarni; Kee, Chee Cheong; Lim, Kuang Lim; Chan , Ying Ying; Teh, Huey Chien; Mohd Yusoff, Ahmad Faudzi; Kaur, Gupreet; Zain, Zarihah; Nik Mohamed, Mohamad Haniki; Salleh, Sallehuddin (BioMed Central, 2013)
Background: Three National Health and Morbidity Surveys (NHMSs) had been conducted in Malaysia in 10-year intervals from 1986–2006. Based on the latest NHMS survey in 2006, we describe the prevalence of smoking and identify the social and demographic factors associated with smoking among adult males in Malaysia. Methods: A cross-sectional study among 15,639 Malaysian adult males aged 18 years and above was conducted using proportional to size stratified sampling method. The socio-demographic variables examined were level of education, occupation, marital status, residential area, age group and monthly household income. Results: The prevalence of smoking among adult males in Malaysia was 46.5% (95% CI: 45.5–47.4%), which was 3% lower than a decade ago. Mean age of smoking initiation was 18.3 years, and mean number of cigarettes smoked daily was 11.3. Prevalence of smoking was highest among the Malays (55.9%) and those aged 21–30 years (59.3%). Smoking was significantly associated with level of education (no education OR 2.09 95% CI (1.67–2.60), primary school OR 1.95, 95% CI (1.65–2.30), secondary school OR 1.88, 95% CI (1.63–2.11), with tertiary education as the reference group). Marital status (divorce OR 1.67, 95% CI (1.22–2.28), with married as the reference group), ethnicity (Malay, OR 2.29, 95% CI ( 1.98–2.66; Chinese OR 1.23 95% CI (1.05–1.91), Other Bumis OR 1.75, 95% CI (1.46–2.10, others OR 1.48 95% CI (1.15–1.91), with Indian as the reference group), age group (18–20 years OR 2.36, 95% CI (1.90–2.94); 20–29 years OR 3.31 , 95% CI 2.82–3.89; 31–40 years OR 2.85 , 95% CI ( 2.47–3.28); 41–50 years OR 1.93, 95% CI (1.69–2.20) ; 51–60 years OR 1.32, 95% CI (1.15–1.51), with 60 year-old and above as the reference group) and residential area (rural OR 1.12 , 95% CI ( 1.03–1.22)) urban as reference. Conclusion: The prevalence of smoking among Malaysian males remained high in spite of several population interventions over the past decade. Tobacco will likely remain a primary cause of premature mortality and morbidity in Malaysia. Continuous and more comprehensive anti-smoking policy measures are needed in order to further prevent the increasing prevalence of smoking among Malaysian men, particularly those who are younger, of Malay ethnicity, less educated, reside in rural residential area and with lower socio-economic status. Keywords: Smoking, Malaysian adult males, Prevalence, Socio-demographic factors